Frequency of Pulmonary Hypertension in Patients with Chronic Kidney Disease Undergoing Hemodialysis - Javeria Shamim, Fatima Zahra, Amna Munir, Fatima Zuhra, Syed Aftab Haider (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of pulmonary arterial hypertension (PAH) in patients with chronic kidney disease (SKD) undergoing hemodialysis. Materials and Methods: A total number of 80 patients of age 16-75 years, either gender presenting with CKD undergoing hemodialysis were included. This study was conducted in the department of nephrology of Nishtar Hospital Multan from June-2021 to February 2022. The patients underwent echocardiography. If there was pulmonary artery systolic pressure >35 mm Hg, then pulmonary hypertension was labeled. Results: Mean age of patients was 48.67±11.71 years. Mean BMI patients was 24.79±3.25 kg/m2. There were 57 (76.00%) males and 18 (24.00%) female patients. 31 (38.8%) out of 80 patients were smokers, diabetes was found in 35 (43.8%) patients. Hypertension was found in 53 (66.3%) patients. Mean pulmonary artery systolic pressure were 29.47±9.16 mmHg. PAH was found in 15 (18.75%) patients. Conclusion: PAH is a common disorder in patients of CKD undergoing maintenance hemodialysis and more than 18% of CKD patients undergoing maintenance HD had PAH.